Valuing Cultural Ecosystem Services in Aruba - Soberón Forsberg, Vanessa Sofía (2025)
A contingent valuation study was conducted to estimate tourists' willingness to pay (WTP) for an environmental fee aimed at enhancing nature protection in Aruba. Stay-Over tourists (staying at least one night) and cruise tourists (visiting without staying overnight) were surveyed. A random sample was used, stratified by nationality for stay-over tourists and a random sample for cruise tourists. Surveys were conducted in person at Aruba's exit points, such as airports and ports. Binomial logistic regression models were applied to assess the likelihood that tourists will contribute to Aruba's conservation, and simple linear regression models were used to estimate WTP.A higher percentage of cruise tourists (52.7%) compared to Stay-Over tourists (47.3%) indicated that they are willing to pay for nature conservation; however, Stay-Over tourists have a higher WTP per visit. This contributes to the total annual WTP being higher for stayover tourists. The estimated annual WTP is US$6.2 million for Stay-Over tourists and US$3.7 million for cruise tourists, totalling US$9.9 million.The variables that most influence WTP are nationality and perception of environmental problems.